PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Purba Tambak, Anastasya Gloria Eure Eka; Aryati, Ana Sofia (Jurnal Kewirausahaan dan Inovasi, 2023)
This research was based on the phenomenon of decreased employee performance at the Hanna Sejahtera Oil Palm Plantation. Intense competition among those engaged in oil palm plantations requires companies to maintain sustainability through employee performance. The purpose of writing this research is to determine the effect of transformational leadership and the work environment on employee performance (a study on Hanna Sejahtera's oil palm plantations). This type of research is explanatory with a quantitative approach. The population of this research is all employees in the research project totaling 300 people. Respondents in this study were taken by random sampling method and amounted to 75 respondents as a sample based on Slovin calculations. This study uses multiple linear regression analysis which has previously been carried out by instrument testing and classical assumption tests. Hypothesis testing is done by using an analysis tool F test and t test. The results of this study indicate that there is a significant influence of Transformational Leadership and the Work Environment on Employee Performance both simultaneously and partially. This research implies that transformational leadership and a well-implemented work environment can improve employee performance at the Hanna Sejahtera Riau Oil Palm Plantation Company.